2014
DOI: 10.1136/bjophthalmol-2014-305101
|View full text |Cite
|
Sign up to set email alerts
|

Functional centre of the upper eyelid: the optimal point for eyelid lifting in ptosis surgery

Abstract: The functional eyelid centre was located slightly temporal to the mid-pupillary line. A better eyelid contour in ptosis surgery is produced when eyelid lifting is centred around the functional eyelid centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
(11 reference statements)
0
3
0
1
Order By: Relevance
“…It has been reported that the marginal peak point in ptotic eyelids moves temporally by the main hanging suture in ELA (8,(19)(20)(21) . Due to the unilateral ptosis design of our study, we noticed that the peak point of the ptotic eyelid shifted nasally in the ELA Group achieving peak point symmetry with the contralateral eyelid.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the marginal peak point in ptotic eyelids moves temporally by the main hanging suture in ELA (8,(19)(20)(21) . Due to the unilateral ptosis design of our study, we noticed that the peak point of the ptotic eyelid shifted nasally in the ELA Group achieving peak point symmetry with the contralateral eyelid.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported a more temporal peak of the upper lid than previously reported [ 15 ], both in healthy subjects [ 16 , 17 ] and patients with thyroid ophthalmopathy [ 18 ]. In addition, multiple studies have reported a slight temporalization of the peak after ptosis correction [ 7 , 17 , 19 , 20 ]. In our study, while the mean peak of the contralateral eye was found to be 1.25 ± 1.55 mm temporal to the center of the pupil, the preoperative mean peak of the ptotic eye was located 0.03 ± 1.57 mm nasal and the postoperative mean peak of the ptotic eye was located 1.87 ± 1.41 mm temporal to the center of the pupil.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, 27,28 supratarsal fixation of the silicone rods at two points resulted in good patient outcomes in frontalis suspension surgery. Kim et al 27 reported the functional centre of the upper eyelid, suggesting its clinical significance when performing ptosis surgery. They demonstrated that the outcome of silicone-rod surgery was excellent when the rod was fixed 4.4 mm nasal and 3.9 mm temporal from the functional eyelid centre.…”
Section: Discussionmentioning
confidence: 99%